IMMUNOPHENOTYPIC CHARACTERISTICS OF INFLAMMATORY BREAST CANCER - A. I. Berishvili; N. N. Tupitsyn; K. P. Laktionov (ABV-press, 2014)
The investigation enrolled 31 patients with inflammatory breast cancer (IBC) treated at the N. N. Blokhin Cancer Research Center from 2006 to 2008. IBC is diagnosed on the basis of signs of rapid progression, such as localized or generalized breast induration, red- ness and edema. IBC accounts for less than 5% of all diagnosed breast cancers and is the most lethal form of primary breast cancer. We studied tumor markers of the immunophenotype of IBC and levels and subpopulations of immunocompetent tumor-infiltrating cells. We found that expression of HLA-DR is in negative correlation with MUC-1 expression and lymphoid cells tumor infiltration is asso- ciated with the increase in T-cell subpopulations.